**Quote:**

Can you also show the solution for *c*?

Here it is.

We start with

*a* = 2

*b*³/

*c*Solve for c:

*c* = 2

*b*³/

*a*Now halve

*a* and double

*b*. In other words plug in

*a*/2 instead of

*a* and 2

*b* instead of

*b*.

?? × *c* = 2(

**2***b*)³/(

*a*/

**2**)

Then get all the new multipliers/dividers at the beginning of the right side. Note that we divide by (

*a*/2), which is the same as multiplying by (2/

*a*), so 2 goes to the numerator.

I've highlighted the new multipliers by the same colors to make transformations easier to spot.

?? × *c* = ( 2(

**8***b*³)/

*a* ) ×

**2**?? × *c* = (

**8** ×

**2**) × ( 2

*b*³/

*a* )

Thus

?? is

8 ×

2 = 16